Protective Role of Nuclear Factor Erythroid 2-Related Factor 2 Against Respiratory Syncytial Virus and Human Metapneumovirus Infections - Ivanciuc, Teodora; Sbrana, Elena; Casola, Antonella; Garofalo, Roberto P. (Frontiers in Immunology, 2018)
The pathogenesis of respiratory syncytial virus (RSV) infections is characterized by lower airway obstruction driven at great extent by the exuberant production of inflammatory cytokines. In studies conducted in vitro, in experimental mouse models and in children with naturally acquired infections we have discovered that in the course of RSV infection reactive oxygen species (ROS) are rapidly generated along with reduction in the expression levels of antioxidant enzymes (AOEs), which are involved in maintaining the cellular oxidant-antioxidant balance. These events were associated with the concomitant reduction in nuclear factor erythroid 2-related factor 2 (Nrf2), a key transcription factor that controls AOE expression. The objective of the current study was to establish the role of Nrf2 in shaping innate immune responses, clinical disease, airway inflammation and viral replication in established experimental models of intranasal RSV and human metapneumovirus (hMPV) infections, by employing mice genetically deficient for the Nrf2 gene. Compared to control wild type (WT), mice genetically deficient in Nrf2 (Nrf2 KO) developed enhanced clinical disease, airway inflammation and pathology, and significantly greater lung viral titers following experimental infection with either RSV or hMPV. In particular, compared to control mice, RSV-infected Nrf2 KO mice lost more body weight and had increased airway obstruction at time points characterized by a remarkable increase in inflammatory cytokines and airway neutrophilia. Airway levels of AOEs and enzymes that regulate synthesis of the endogenous hydrogen sulfide (H2S) pathway, which we showed to play an important antiviral function, were also decreased in RSV-infected Nrf2 KO compared to WT. In conclusion, these results suggest that Nrf2 is a critical regulator of innate, inflammatory, and disease associated responses in the airways of mice infected with viruses that are members of the Paramyxoviridae family. Importantly, the results of this study suggest that Nrf2-dependent genes, including those controlling the cellular antioxidant and H2S-generating enzymes and cytokines can affect several aspects of the antiviral response, such as airway neutrophilia, clinical disease, airway obstruction, and viral replication.